The questions of allergy and anti-tuberculosis immunity in the works of M.M. Tsehnovitser - Kuchma, I; Moiseenko, T (Annals of Mechnikov's Institute, 2020)
The mechanism of anti-tuberculosis immunity drew the attention of scientists since the established of the infectious nature of tuberculosis. The famous ukrainian microbiologist and immunologist M.M. Tsehnovitser in period from 1921 to 1940 years spent a lot of original experiments for elucidation of the role of allergy in the anti-tuberculosis immunity. M.M. Tsehnovitser believed that a common cause of infectious allergy is tuberculosis granuloma, which even at rest eliminated weakened microbes and their products in general lymphatic and blood stream of the body. In his experiments M.M. Tsehnovitser discovered: 1 When the body comes in contact with M.tuberculosisi formed tuberculosis centre. Infection meets local tissue reaction and in incubation period formed sensitization. In this state the body manifested as a natural susceptibility and resistance to infection. During this period organism going through the initial stage of allergy. 2. Meanwhile, the infectious process goes on and the M.tuberculosisi giving rise. The body reacts to this change in the formula blood - leukocytosis, monocytosis, eosinophilia. Tuberculosis focus represents a formed granuloma. This phase of tuberculosis infection accompanied by severe allergy. 3. Then there are two versions of the process. In the first case happened the generalization of tuberculosis infection. The blood reacts are leukopenia, monocytosis, eosinophilia and lymphocytosis due to toxic processes. In the second case M.tuberculosi multiplied only local in the granuloma and is not generalization of tuberculosis process. In this case, natural immunity is raised. There are allergy and positive anergy in later. 4. It is exclusively unique phenomenon for tuberculous process is the regression of the fire with his sterilization. This type of tuberculous process is in BCG-infection. In the source of infection observed complete resolution of pathological tissue, blood initially reacts slightly, but quickly comes back to normal. There is a natural infectious immunity and allergic states. M.M. Tsehnovitser made the following conclusions: 1. Tuberculosis allergy arise in infected organism as index and indicator of infection, accompanied by acquired immunity. 2. Receptive cells at the time of exposure to tuberculosis antigens produced toxic complex (such as histamine) that caused local tissue sensitization (by action on the walls of capillaries and nerve endings) and total allergic reactions. 3. Tuberculosis allergy stimulates innate immunity. 4. Receptive tissue and blood cells at the time of contact with tuberculosis allergens intensified sharp phagocytic reaction which retards the spread in the body of the allergen. 5. Tuberculosis allergy plays a role in the body's fight against tuberculosis.